The participation of children and young people in care: insights from an analysis of national inspection reports in the Republic of Ireland. Issue 1 (2nd January 2019) - Brady, Bernadine; Kennan, Danielle; Forkan, Cormac; Tierney, Edel; Jackson, Rebecca; Holloway, Rowan
ABSTRACT: The term "participation" is widely used to refer to the involvement of children and young people in decision-making on issues that affect their lives. The Health and Information Quality Authority (HIQA) is the national inspectorate for social care in Ireland. HIQA monitors Tusla, Ireland's child and family agency, for compliance with national children's standards, including standards on children and young people's participation rights. This paper outlines findings of a secondary analysis of data in relation to participation standards in HIQA foster care, residential care and special care inspection reports over a two-year period from 2013 to 2015 ( n  = 40). The thematic analysis explores the degree to which the reports found that children in care are provided with the opportunity to influence decisions in relation to their everyday lives, to participate in child in care reviews, receive information, avail of advocacy services and have access to a complaints mechanism. While there is much evidence of good practice across all sectors, some notable differences between the realisation of participation standards in residential care and foster care were found. This baseline analysis was undertaken prior to the implementation of a comprehensive participation strategy by Tusla across the organisation and highlights areas in which practice can be improved or mainstreamed in this work programme.